Temperature-Dependence of Glyphosate-Based Herbicide's Effects on Egg and Tadpole Growth of Common Toads - Baier, Fabian; Jedinger, Mathias; Gruber, Edith; Zaller, Johann G. (Frontiers in Environmental Science, 2016)
Glyphosate-based herbicide formulations are broadly used in agriculture, silviculture, horticulture as well as in private gardens all over the world, thus posing the risk of potential contamination of nearby aquatic bodies inhabited by amphibians. Concurrently, climate change can be expected to alter the temperature of amphibian breeding sites. However, while either glyphosate-based herbicides or temperature have been shown to separately affect the development of amphibians, very little is known on possible interactive effects. We studied the impact of herbicide concentrations and temperature on growth and development of eggs and tadpoles of the Common toad (Bufo bufo L.). We hypothesized that (i) eggs would be better protected against herbicides than tadpoles because of their jelly coating, (ii) that higher temperatures would reduce potential herbicide effects because of an accelerated growth and a lower sensitivity of larger specimens. We conducted one experiment starting with eggs (Gosner stage, GS 9) and another experiment starting with tadpoles (GS 21-24) using a full factorial design with 5 concentrations of the herbicide formulation Roundup® LB Plus (0 mg acid equivalent L-1, 0.5 mg a.e. L-1, 1.0 mg a.e. L-1 or 1.5 mg a.e. L-1 and a pulse treatment with 3-4 times addition of 0.5 a.e. mg L-1 over the course of several weeks) and two temperature levels (15°C and 20°C). Contrary to our expectation, our results showed that toad eggs are more sensitive to herbicides than tadpoles leading to an averaged 31% increase in total length, tail length and body length compared to the herbicide-free control. Tadpole morphology, development or mortality was not influenced by herbicides. Higher temperature accelerated growth of both eggs and tadpoles. This is among the first study showing interactive effects between herbicides and temperature especially for egg development resulting in more pronounced herbicide effects at lower temperatures than at higher temperatures.